Pharmaceutical Industry Development in the Midst of Crisis: Global Trends - Z. A. Mamedyarov (Модернизация, инновация, развитие, 2020)
Purpose: the main purpose of the article was to study the trends in the global pharmaceutical industry, as one of the most knowledge-intensive in the world economy, against the background of the 2020 COVID-related crisis. The task was to study the impact of the economic crisis on the priorities of the largest pharmaceutical multinationals, to link them with trends in the restructuring of health care systems, as well as to analyze and assess the potential impact of Brexit on the European pharma industry, starting from 2021.Methods: the work is based on a comparative analysis of trends in the restructuring of global value chains in pharmaceuticals, the digitalization of pharmaceuticals and health care, as well as a quantitative analysis of the revenue and value added by the largest European pharmaceutical multinational companies.Results: the COVID-19 pandemic has accelerated the process of digitalization of big pharma; the intensified transition to a continuous production model can be expected in the coming years. Also, the second largest industry market, the EU-27, will suffer less from Brexit than the UK itself, and industries in developing countries will benefit from additional growth opportunities. The digitalization of healthcare remains an important underlying factor for the transformation of pharmaceuticals and further growth of innovation competition. This paper presents the problems of pharma and how to address them, as well as possible ways to restructure healthcare systems to reduce the likelihood of new pandemics – this will be at the heart of regulatory solutions in the medium term.Conclusions and Relevance: governments and state regulators will be actively involved in the process of recovery of the pharmaceutical industry after the crisis. For small regional pharmaceutical producers in developing countries there is a growing need to digitalize production and diversify supply chains. Implementation of continuous production technologies allows expecting growth in the number of small pharmaceutical producers, deepening competition in the industry. The Brexit deal will also have significant implications for the industry, leading to a restructuring of supply chains within the EU from early 2021, reducing the UK's competitiveness.